Depression symptoms and resilience among older adult with chronic illness in UiTM Medical Center / Muhammad Khairil Azfar Othman ... [et al.] - Othman, Muhammad Khairil Azfar; Mazlan, Maz Nur Nadjmi; Armyru Zaman, Muhamad Haziq (2018)
Introduction: The population among older people continue to grow globally and the prevalence of depressive symptoms among these geriatric population has increased including those with chronic illness. Limited number of research was done among the elderly which investigate the relationships between depression and resilience. Objective: The purpose of this study was to determine the relationship between the level of depression and resilience among chronically ill elderly individuals and its associations to sociodemographical characteristics. Methods: A cross-sectional study was designed for this study, was conducted among 218 inpatients and outpatients with a chronic health problem who were 60 years old and above in UiTM Medical Center, Sungai Buloh. The level of depression was assessed using the Malay version of Geriatric Depression Scale 15 (M-GDS-15) whereas the level of resilience was utilized by the Malay version of Connor-Davidson Resilience Scale 25 (CD-RISC-25) and associated sociodemographical factors were also included. Result: The analyzed data shown that out of 218 subjects, 36 or 16.4% were depressed and high level of resilience were found among the subjects with a total mean score of 77.41 (SD=8.35). Two of the sociodemographical factors were found to be significantly associated with depression. Elderly Indian patients were most depressed, followed by Chinese and Malay (mean±SD, 5.00±1.95; 3.69±2.52; 3.05±2.16 respectively) and the elderly with higher number of chronic illness presents higher depression level (r = 0.18, p<0.05). Meanwhile, resilience was significantly associated with gender where females were more resilience than male (mean±SD, 78.82±8.26; 76.29±8.28). Significant and weak negative correlation was found between depression and resilience level among the study samples (r = -0.21, p<0.05). Conclusion: Depression level was influenced by type of race and the number of chronic illness whereas resilience level was influenced by gender. An association between greater depression symptoms and less resilience level was identified. Depression screening among the elderly is necessary to offer them the appropriate treatment and importance of implementing interventions that would promote resilience in older adults needs to be emphasized in preventing uprising geriatric depression.